2015
DOI: 10.1088/0964-1726/24/12/125026
|View full text |Cite
|
Sign up to set email alerts
|

Bond slip detection of concrete-encased composite structure using shear wave based active sensing approach

Abstract: Concrete-encased composite structure exhibits improved strength, ductility and fire resistance compared to traditional reinforced concrete, by incorporating the advantages of both steel and concrete materials. A major drawback of this type of structure is the bond slip introduced between steel and concrete, which directly reduces the load capacity of the structure. In this paper, an active sensing approach using shear waves to provide monitoring and early warning of the development of bond slip in the concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 20 publications
1
71
1
Order By: Relevance
“…Qin et al [46] studied the bond-slip detection between concrete beams and a steel plate using piezoceramic smart aggregates. Zeng et al [47] performed bond-slip detection between concrete and steel using shear mode smart aggregates. Xu et al [48] discovered that the active sensing method can monitor the bond slip between concrete structures and the glass fiber reinforced polymer (GFRP) bars accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al [46] studied the bond-slip detection between concrete beams and a steel plate using piezoceramic smart aggregates. Zeng et al [47] performed bond-slip detection between concrete and steel using shear mode smart aggregates. Xu et al [48] discovered that the active sensing method can monitor the bond slip between concrete structures and the glass fiber reinforced polymer (GFRP) bars accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this hybrid structure had been systematically studied . A series of researches were carried out to reveal the seismic performance, failure mode, dynamic characteristics, and so on . Sun, Zou, and Wang found that both extension length and area ratio of shape steel obviously influenced the bearing capacity of hybrid structure.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the losses of motion stability and the loss of vertical bearing capacity were taken as criterions to judge the collapse of structures [20]. A stress wave-based active sensing method was also used to detect damage in concrete structures [21][22][23][24][25][26][27]. The piezoelectric smart aggregates were adopted for structural health monitoring [28][29][30].…”
Section: Introductionmentioning
confidence: 99%